Elgamal Elliptic Curve Based Secure Communication Architecture for Microgrids - Sarmadullah Khan; Rafiullah Khan (Energies, 2018)
Microgrids play an important role in today’s power systems as the distributed generation is becoming increasingly common. They can operate in two possible modes: (i) standalone and (ii) grid-connected. The transitional state from standalone to grid-connected mode is very critical and requires the microgrid to be synchronized with the main grid. Thus, secure, reliable and trustworthy control and communication is utmost necessary to prevent out-of-sync connection which could severely damage the microgrid and/or the main grid. Existing solutions consume more resources and take long time to establish a secure connection. The objective of the proposed work is to reduce the connection establishment time by using efficient computational algorithms and save the resources. This paper proposes a secure authentication and key establishment mechanism for ensuring safe operation and control of the microgrids. The proposed approach uses the concept of Elgamal with slight modification. Private key of the sender is used instead of a random number. The proposed modification ensures the non repudiation. This paper also presents a system threat model along with security network architecture and evaluates the performance of proposed algorithm in protecting microgrid communication against man in the middle attacks and replay attacks that could delay the packets to damage the system and need to be detected. Mathematical modeling and simulation results show that the proposed algorithm performs better than the existing protocols in terms of connection establishment, resource consumption and security level.